Effect of gamma irradiation on Schottky-contacted vertically aligned ZnO nanorod-based hydrogen sensor. (15th July 2016) - Ranwa, Sapana; Barala, Surendra Singh; Fanetti, Mattia; Kumar, Mahesh
Abstract: We report the impact of gamma irradiation on the performance of a gold Schottky-contacted ZnO nanorod-based hydrogen sensor. RF-sputtered vertically aligned highly c -axis-oriented ZnO NRs were grown on Si(100) substrate. X-ray diffraction shows no significant change in crystal structure at low gamma doses from 1 to 5 kGy. As gamma irradiation doses increase to 10 kGy, the single crystalline ZnO structure converts to polycrystalline. The photoluminescence spectra also shows suppression of the near-band emission peak and the huge wide-band spectrum indicates the generation of structural defects at high gamma doses. At 1 kGy, the hydrogen sensor response was enhanced from 67% to 77% for 1% hydrogen in pure argon at a 150 °C operating temperature. However, at 10 kGy, the relative response decreases to 33.5%. High gamma irradiation causes displacement damage and defects in ZnO NRs, and as a result, degrades the sensor's performance as a result. Low gamma irradiation doses activate the ZnO NR surface through ionization, which enhances the sensor performance. The relative response of the hydrogen sensor was enhanced by ∼14.9% with respect to pristine ZnO using 1 kGy gamma ray treatment.